EDITORIAL - MG Manfredi-Romanini (European Journal of Histochemistry)
We have projected this issue of volume 44 of the European Journal of Histochemistry, the first issue of the third millennium, to celebrate the achievements of the just-ended twentieth century, quite agreed upon as the century of histochemistry. The issue opens with a review by van der Ploeg entitled “Cytochemical nucleic acid research during the twentieth century”. This is the text of a lecture he presented in Camerino to the 1999 Congress of Histochemistry on the occasion of his receiving the 1st International Histochemical Award. The award, in memory of the founder of our Society, Maffo Vialli, was instituted for the express purpose of linking more closely our Society with other European histochemical centers, and more generally with their cell biology activities. Prof. van der Ploeg in his article traces a very analytical history of the last century’s research on nucleic acids and, through this, how our knowledge about cell biology and about how life is regulated, progressed. He begins right from the discovery at the end of the seventeenth century of a simple microscope, “insensitive to optical aberration”, which permitted Van Leeuwenhoek to observe unicellular organisms for the first time. From this follows, clearly and compellingly, the evolution of biological thought about the nucleus and cell life, closely correlating it with the development of the instruments of observation and measurement, and the techniques of imaging and quantification of nucleic acids.